Cultural Heritage Management of Cirebon Sang Cipta Rasa Mosque - Rayi Kinasih, Ade Ika; Khairune Nisa, An Nuur; Nufail Naisaburi, Muhammad; Muhammad, Muhammad; El Adiby Zulqudsie, Faiz Reyhan; Sekar Widyawati, Vania (Ann Publisher, 2024)
Every region in this region has a distinct culture that has been passed down through the ages. Extinct cultures exist, and cultures continue to exist now. Cultural landmarks in Cirebon include the Sang Cipta Rasa Mosque. The Sang Cipta Rasa mosque's management strategies for protecting the city of Cirebon's cultural heritage have been detailed based on field research. Known for its rhombic ornate motifs known as adhan put, this mosque is distinguished by its nine incredibly short doorways. Symbolizing history, science, education, religion, and culture, this mosque is one of the few remaining examples of Islamic civilization on the island of Java. In terms of strengthening the nation's identity, it also has cultural significance.